Combined "Abrarov/Quine-Schreier-Kuntz (AQSK)" algorithm for the calculation of the Voigt function. (September 2021) - Pliutau, Denis
Highlights: Combining algorithms of Abrarov / Quine and Kuntz using method by Schreier. Use Abrarov / Quine and Kuntz algorithms in place of those by Weideman and Humlíček. Voigt profile algorithm for lower processing power hardware targeting HITRAN. Abstract: In this note it is suggested that the complex number rational approximations of Weideman and Humlíček may be replaced with the real number approximations of Abrarov / Quine and Kuntz respectively in the technique suggested by F. Schreier (JQSRT 112(6) (2011) 1010–1025) to provide an accurate Voigt function calculation algorithm with reduced calculation time targeting HITRAN database calculations. The resulting algorithm may be useful in applications using electronics with lower processing power.